The Influence of Outpatients Medical Information Completeness in The Emergency Departments and Policlinics on Returning BPJS Health Claim Status - Faik Agiwahyuanto; Maulana Tomy Abiyasa; Adian Khoironi; Ester Widhiatmi Sutiningary (MEDIA ILMU KESEHATAN, 2022)
Background: Returning BPJS Health claim status required some outpatients data, therefor this study conducted to understand the medical information needed for the BPJS Health claim.Objective: The objective of this paper was returning BPJS Health claim status required some outpatients data, therefor this study conducted to understand the medical information needed for the BPJS Health claim.Methods: Retrospective analysis with quantitative approach. Variables were groups of cases in the form of confirmation from BPJS Health related to reviews on pending claim files, differentiated according to the type of case. As far as observations could be grouped into 8 confirmation groups as the theme of the cases taken 396 samples of pending claim files at XXX Hospitals Semarang Central Java Indonesia. Data collection was obtained from observations. Data analysis used quantitative analysis.Results: 16.9% were confirmation related to Z code as diagnosis, 11.1% were confirmation of secondary codes, 17.2% were confirmation of potential outpatient and inpatient care, 7.6% were system confirmation, 11.6% were confirmation related to medical support, 11.1% were confirmation regarding number of visits, 5.3% were confirmation related to medical actions, and 19.2% were other confirmations, which contains about authentication, administrative documents, patient identity.Conclusion: Completeness of medical information on outpatients from emergency departments and polyclinic of BPJS Health patients were confirmation related to Z code as diagnosis, confirmation of secondary codes, confirmation of potential outpatient and inpatient care, system confirmation, confirmation related to medical support, confirmation regarding number of visits, confirmation related to medical actions, and other confirmations.